Book review: Biruk, C. 2018: Cooking Data: Culture and Politics in an African Research World. (January 2020) - Natasha S.K.,
Biruk, C. 2018: Cooking Data: Culture and Politics in an African Research World . Durham and London: Duke University Press. 277 pp. $26.95. ISBN: 9780822370895.